Between the rose and the shoulders of giants - Garza Mercado, Román (UANL. Facultad de Medicina, 2014)
The following are thoughts on 2 of the most well-known phrases in the English language, recognized as universal academic icons. That of Juliet Capuleto’s in Act II, scene II, “The Balcony”, in the immortal work of William shakespeare’s Romeo and Juliet about “A rose by any other name”, and “On the shoulders of giants”, traditionally attributed to Isaac Newton, the discoverer of the Mechanical Universal Laws, including that of Universal Law of Gravitation, in the 17th Century, but in reality first said by the humanistic philosopher and theologist Bernard of Chartres in the 12th Century